Diversity and Habitat Distribution of Birds in Coastal Marshes and Comparisons with Surrounding Upland Habitats in Southeastern South America - Isacch, Juan Pablo (2014)
We studied variation in bird assemblages with plant associations for three different coastal marshes from Southeastern South America (SESA) and assessed how marsh bird assemblages related to nearby upland bird assemblages. We surveyed bird species and plant structure along the tidal gradient of each locality from the low tide level to the upper habitats bordering coastal marshes. Twenty species frequently used coastal marshes, including relatively few migratory species. We found that birds occurring in SESA coastal marshes do not have distributions constrained to coastal marshes. Nonetheless, four bird assemblages were recognized in association with vegetation types and/or sites. Among the recorded coastal marsh species, the bay-capped wren-spinetail (Spartonoica maluroides) is both the most frequent and the most habitat constrained. Bird richness increases steadily along the tidal gradient associated with the increase in vegetation structure, suggesting that bird richness is directly explained by vegetation and indirectly by the physical conditions influencing vegetation structure. Results highlight the importance of SESA middle marshes as habitat for conservation of some threatened SESA grassland birds.